Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
6x ( 3x + 1) - 216 (3x + 1) = 0 (đề vậy đúng không?)
(3x +1) (6x - 216) = 0
(3x + 1) 6(x - 36) = 0
3x +1 = 0 hay x - 36 = 0
x = \(\frac{-1}{3}\) hay x = 36
d) \(\left(7-2x\right)^2=49\)
\(\Rightarrow\left(7-2x\right)^2=\left(\pm7\right)^2\)
\(\Rightarrow\left[{}\begin{matrix}7-2x=7\\7-2x=-7\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=7-7\\2x=7+7\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=0\\2x=14\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=7\end{matrix}\right.\)
e) \(\left(9-x\right)^3=216\)
\(\Rightarrow\left(9-x\right)^3=6^3\)
\(\Rightarrow9-x=6\)
\(\Rightarrow x=9-6\)
\(\Rightarrow x=3\)
g) \(6^{x+2}+6^x=1332\)
\(\Rightarrow6^x\cdot\left(6^2+1\right)=1332\)
\(\Rightarrow6^x\cdot37=1332\)
\(\Rightarrow6^x=1332:37\)
\(\Rightarrow6^x=36\)
\(\Rightarrow6^x=6^2\)
\(\Rightarrow x=2\)
\(d,\left(7-2x\right)^2=49\)
\(\Leftrightarrow\left[{}\begin{matrix}7-2x=7\\7-2x=-7\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}2x=0\\2x=14\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=7\end{matrix}\right.\)
\(e,\left(9-x\right)^3=216\)
\(\Leftrightarrow\left(9-x\right)^3=6^3\)
\(\Leftrightarrow9-x=6\)
\(\Leftrightarrow x=3\)
\(f,6^{x+2}+6^x=1332\)
\(\Leftrightarrow6^x\left(6^2+1\right)=1332\)
\(\Leftrightarrow6^x\cdot37=1332\)
\(\Leftrightarrow6^x=36\)
\(\Leftrightarrow6^x=6^2\)
\(\Leftrightarrow x=2\)
#Urushi
a) ( x + 216 ) : 61 + 1 = 202
( x + 216 ) : 61 = 201
( x + 216 ) = 12261
x = 12045
b) 1818 : ( 6x - 37 ) + 1 = 19
1818 : ( 6x - 37 ) = 18
( 6x - 37 ) = 101
6x = 138
x = 23
c) ( x : 23 + 45 ) x 67 + 3 = 8914
( x : 23 + 45 ) x 67 = 8911
x : 23 + 45 = 133
x : 23 = 88
x = 2024
(x + 216) : 61 + 1 = 202
=> (x + 216) : 61 = 201
=> x + 216 = 12261
=> x = 12045
vậy_
1818 : (6x - 37) + 1 = 19
=> 1818 : (6x - 37) = 18
=> 6x - 37 = 101
=> 6x = 138
=> x = 23
vậy_
(x : 23 + 45) x 67 + 3 = 8914
=> (x : 23 + 45) x 67 = 8911
=> x : 23 + 45 = 133
=>x : 23 = 88
=> x = 2024
vậy_
https://hoc24.vn/cau-hoi/a-5x-2x-62-50b-5x-x-150-2-3c-6x-x-511-59-31d-5x-3x-36-334-124x-2x-68-219-216.2785429565572
a: \(\Leftrightarrow7x=35\)
hay x=5
b: \(\Leftrightarrow6x=78\)
hay x=13
a) 4x + 3x = 217
x( 4 + 3 ) = 217
7x = 217
x = 217 : 7 = 31
Vậy x = 31
b) 9x - 3x = 216
( 9 -3)x = 216
6x = 216
x = 216:6 = 36
Vậy x = 36
c) 6x - 3x + 23 = 230
( 6 - 3 )x = 230 - 23
3x = 207
x = 207 : 3 = 69
Vậy x = 69
d) 5x + 3x + x = 72
5x + 3x + 1x = 72
( 5 + 3 + 1 )x = 72
9x = 72
x = 72 : 9 = 8
Vậy x = 8
Chúc bạn học tốt nhé
a) \(4x+3x=217\)
\(\Rightarrow x\cdot\left(3+4\right)=217\)
\(\Rightarrow7x=217\)
\(\Rightarrow x=\dfrac{217}{7}\)
\(\Rightarrow x=31\)
b) \(9x-3x=216\)
\(\Rightarrow x\cdot\left(9-3\right)=216\)
\(\Rightarrow6x=216\)
\(\Rightarrow x=\dfrac{216}{6}\)
\(\Rightarrow x=36\)
c) \(6x-3x+23=230\)
\(\Rightarrow x\cdot\left(6-3\right)=230-23\)
\(\Rightarrow3x=207\)
\(\Rightarrow x=\dfrac{207}{3}\)
\(\Rightarrow x=69\)
d) \(5x+3x+x=72\)
\(\Rightarrow x\cdot\left(5+3+1\right)=72\)
\(\Rightarrow9x=72\)
\(\Rightarrow x=\dfrac{72}{9}\)
\(\Rightarrow x=8\)
672-(6x-108)=216
6x-108 = 672-216
6x-108 = 456
6x = 456+108
6x = 564
x = 564:6
x = 94
672 - [6x - 108] = 216
6x - 108 = 672 - 216
6x - 108 =456
6x = 456 + 108
6x =564
x = 94